Evaluation of the antidiarrheal activity of the 80% hydromethanolic crude extract and solvent fractions of Terminalia brownii Fresen (Combretaceae) leaves in Swiss Albino mice - Kassaw, Khalid Ibrahim; Wondafrash, Dawit Zewdu; Yesuf, Jibril Seid; Mengistie, Mestayet Geta (Frontiers in Pharmacology, 2025)
BackgroundAlthough diarrhea is a preventable disease, it continues to have a significant impact on global health, with the burden being much greater in Sub-Saharan Africa. Medicinal plants represent affordable and locally available resources to address many diseases, including diarrhea. Thus, this study aimed to investigate the antidiarrheal activities of the 80% hydromethanolic crude extract and solvent fractions of Terminalia brownii Fresen (Combretaceae) leaves in Swiss Albino mice.MethodsThis study was carried out by administering the 80% hydromethanolic crude extract and solvent fractions from the crude extract, including the n-hexane fraction (NHF), ethyl acetate fraction (EAF), and aqueous fraction (AF) at doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg, respectively, to the mice. The effects of these extracts and solvent fractions on reducing/delaying diarrhea were compared with the impact of the solvent used for reconstitution and a standard drug (loperamide 3 mg/kg or atropine 5 mg/kg), as well as with each other.ResultsThe hydromethanolic crude extract and ethyl acetate fraction at all tested doses significantly reduced wet defecation (P < 0.05). In addition, total defecation was significantly reduced at a dose of 200 mg/kg (P < 0.05) and 400 mg/kg (P < 0.001) of the crude extract and ethyl acetate fraction at all tested doses (P < 0.01. The aqueous fraction at 200 mg/kg and 400 mg/kg and the n-hexane fraction at 400 mg/kg (P < 0.05) significantly inhibit wet and total defecation. Likewise, in the enteropooling test, the crude extract and ethyl acetate fractions showed a significant reduction in the weight and volume of intestinal contents at a dose of 200 mg/kg (P < 0.05) and 400 mg/kg (P < 0.05). Castor oil-induced intestinal motility was significantly reduced (p < 0.001) by the crude extract and ethyl acetate fractions at all tested doses.ConclusionThe result from this study suggests significant antidiarrheal activity of Terminalia brownii leaves, which validates its traditional use. The 80% hydromethanolic crude extract and ethyl acetate solvent fractions of Terminalia brownii Fresen leaves have shown better antidiarrheal activity.